Bioactive compounds and total antioxidant activity of Cornus alba leaf extracts - Buran, Abayhan; Topdemir, Aykut; Öztürk, Rabia (My University, 2022)
In this study, total phenolic content (TPC), total flavonoid content (TFC), total antioxidant capacity (TAC), chlorophyll-a amount, chlorophyll-b amount, total chlorophyll amount and total carotenoid content of leaf extracts of Cornus alba (dogwood), which is widely used as an ornamental plant, were investigated. Distilled water, ethanol, methanol and acetone solvents were used for the extraction of leaves. The leaves were extracted with acetone for total chlorophyll and total carotenoid analysis. Folin-Ciocalteu method was used for total phenolic substance analysis. AlCl3 method was used in total flavonoid analysis and ABTS method was used to determine total antioxidant capacity. The highest TPC was obtained from the water extract as 39.09±0.36 mg GAE/g dry mass. The highest TFC was obtained from ethanol extracts as 65.28±0.61 mg QE/g dry mass. The highest TAC was obtained from water extracts as 9.39±0.07 mmol TEAC/g dry mass. The total amount of chlorophyll in C. alba leaves is 2.65±0.12 mg/g, the amount of chlorophyll-a 0.59±0.04 mg/g, the amount of chlorophyll-b 1.15±.06 mg/g and total carotenoid amount was calculated as 0.43±0.01 mg/g. Total phenolic content, total flavonoid content and total antioxidant capacity of C. alba (dogwood) plant were found to be significant. These bioactive ingredients are widely used in cosmetics, medicine, food additives, etc. suitable for use.
Bildiri - Yayımlanmış
Keywords: Cornus alba; Total Phenolic; Flavonoid; Antioxidant; Leaf extract